Evaluation of Educational Tourism Based on Agribusiness In Community Forest Areas - Anang Susanto; Indah Rekyani Puspitawati (International Journal of Science and Environment (IJSE), 2021)
The development of educational tourism is an urgent matter; many sectors of life are automatic will play a role. Educational tourism is developing, so from an economic point of view, the community's economy will also increase. The local population, the majority of whom are farmers, is very important for playing an active role in the development of educational tourism to benefit and impact farmers to improve their welfare. This research aims to describe how the evaluation of educational tourism activities in the Madiun district. This research method is qualitative with a case study approach. The results showed that farmers participated in the development of educational tourism, starting from the planning stage to the evaluation. The success of community-based educational tourism development in Madiun Regency is inseparable from promotion and development society, both from the ecological, economic, socio-cultural, and political aspects